A Comprehensive Grammar of the English Language - Quirk, Randolph [et al.]; Indexed By: David Crystal (London Pearson, 2010)
A comprehensive grammar of the english language is the mostthorough and most definitive grammar of modern english everwritten. Professors quirk, greenbaum, leech, and svartvik, who areacknowledged to be leading authorities in the field of englishlanguage, have made this the climax of twenty years ofcollaborative work. Building on the strength of their previouswork, especially a grammar of comprehensive english ? unchallengedsince its publication in 1972 as the standard reference work in thefield ? the authors have produced an even more comprehensive andperceptive synthesis of current grammatical description. They havedrawn collectively on the most recent research, including newfindings not only in grammar but also in the neighbouring fields ofsemantics, pragmatics, and text linguistics.
Include Index and Bibliography
A Comprehensive Grammar of the English Language contains a survey of english grammar, verbs and auxiliaries and nouns and pronouns etc.
Keywords: English language--Grammar